(untitled) (EAI Endorsed Transactions on Scalable Information Systems, 2026)
Correction to: Hongcai Chen et al. (2026) A Vehicle Target Tracking Method for Roadside Millimeter-Wave Radar. https://doi.org/10.4108/eetsis.13388 Due to typesetting errors, some of the formulas in sections 2.2.2 and 2.3.1 of this article did not display correctly. These errors were corrected and the original article has been updated.